The effects of two game interaction modes on cortical activation in subjects of different ages : a functional near-infrared spectroscopy study - Ge, Ruhong (2021)
Increasing age and various pathological factors lead to cognitive function decline among the elderly. The most serious cognitive dysfunctions among the elderly include mild cognitive impairment (MCI), Alzheimer's disease (AD), and vascular dementia (VAD). Cognitive training is an effective approach to mitigate the decline in cognitive function. Recent studies have confirmed that emerging training methods using new technologies, such as virtual reality (VR) and mobile phones, can be used effectively for cognitive training. This study used functional near-infrared spectroscopy (fNIRS) to compare the brain activation of young and elderly people during VR and mobile phone training when performing a cognitive training game. fNIRS has been shown to be an effective tool for monitoring cognitive decline. In the current study, the MMSE scale was used to measure cognitive performance and fNIRS was used to measure brain activation among 20 youth (mean age 25.33± 1.59 years) and 17 elderly people (mean age 63± 4.35 years). The results showed that the mobile phone game produced significant activation of the prefrontal lobe (PFC) and the VR game produced significant activation of the parietal lobe (MC). The average MMSE scale score of the elderly group was lower than that of the young group and was strongly correlated with PFC activation. This study confirms that elderly people have reduced cognitive function compared to young people. The results indicate that mobile phone games have a positive training effect on reducing cognitive decline, and that VR is a suitable means for cognitive function training among the elderly.